Sustainable Urban Drainage: a brief review of the compensatory techniques of structural and non-structural measures - Albuquerque, Mariana Borges (2019)
The accelerated disorderly and unplanned growth of cities has had negative impacts, such as the inability of the rainwater collection network to drain the area, causing flooding. Developing sustainable urban drainage projects, integrated urban water management and compensatory techniques in urban drainage are alternatives used to reduce the negative effects of urbanization on the hydrological cycle. Planning the surface runoff of urban water should go beyond structural projects, we must consider technical, financial, political and cultural aspects, among others, which makes this process complex, although very necessary. The aim of this paper is to undertake a brief literature review presenting the main urban drainage compensatory techniques used to promote sustainable management of rainwater. It concludes that there are many compensatory techniques that can be applied to promote and make sustainable urban drainage possible, whether through structural or non-structural measures.